Immaginare una nuova nazione: strategie politiche e costruzione dell'identità etnica in Sud Sudan - Nicola Martellozzo (Im@go. A Journal of the Social Imaginary, 2020)
The African context is an avant-garde geopolitical laboratory, where the inherited state forms of the colonial period are reworked and transformed through political imaginary. The case of South Sudan is particularly interesting: its birth and its development followed a projectuality elaborated during half a century of civil conflict, in which a complex social imaginary was formed. In this article, we want to highlight two closely related aspects. The first is linked to the charismatic figure of John Garang, leader of the SPLA/M. At his death Garang was consecrated as a popular hero and founding figure, becoming a primary reference in the imaginary of the new nation. The second aspect concerns the political strategy of President Salva Kiir, which breaks with the previous nationalist project. In recent years, the formation of an ethnic imaginary transformed local communities into territorial identities, interpreting the socio-political clash through an ethnic category created by colonialism and reproduced during the Sudanese civil wars.